Association between hospital post-resuscitative performance and clinical outcomes after out-of-hospital cardiac arrest. (July 2015) - Stub, Dion; Schmicker, Robert H.; Anderson, Monique L.; Callaway, Clifton W.; Daya, Mohamud R.; Sayre, Michael R.; Elmer, Jonathan; Grunau, Brian E.; Aufderheide, Tom P.; Lin, Steve; Buick, Jason E.; Zive, Dana; et al.
Abstract: Background: Survival varies among those resuscitated from out-of-hospital cardiac arrest (OHCA). Evidence-based performance measures have been used to describe hospital quality of care in conditions such as acute coronary syndrome and major trauma. It remains unclear if adherence to performance measures is associated with better outcome in patients hospitalized after OHCA. Objectives: To assess whether a composite performance score based on evidence-based guidelines for care of patients resuscitated from OHCA was independently associated with clinical outcomes. Methods: Included were 3252 patients with OHCA who received care at 111 U.S. and Canadian hospitals participating in the Resuscitation Outcomes Consortium (ROC-PRIMED) study between June 2007 and October 2009. We calculated composite performance scores for all patients, aggregated these at the hospital level, then associated them with patient mortality and favorable neurological status at discharge. Results: Composite performance scores varied widely (median [IQR] scores from lowest to highest hospital quartiles, 21% [20%, 25%] vs. 59% [55%, 64%]. Adjusted survival to discharge increased with each quartile of performance score (from lowest to highest: 16.2%, 20.8%, 28.5%, 34.8%, P  < 0.01), with similar findings for adjusted rates of good neurologic status. Hospital score was significantly associated with outcome after risk adjustment for established baseline factors (highest vs. lowest adherence quartile: adjusted OR of survival 1.64; 95% CI 1.13, 2.38). Conclusions: Greater survival and favorable neurologic status at discharge were associated with greater adherence to recommended hospital based post-resuscitative care guidelines. Consideration should be given to measuring, reporting and improving hospital adherence to guideline-based performance measures, which could improve outcomes following OHCA.